Utilization of CRISPR-Cas genome editing technology in filamentous fungi: function and advancement potentiality - Shen, Qiqing; Ruan, Haihua; Zhang, Hongyang; Wu, Tao; Zhu, Kexin; Han, Wenying; Dong, Rui; Ming, Tianwei; Qi, Haikun; Zhang, Yan (Frontiers in Microbiology, 2024)
Filamentous fungi play a crucial role in environmental pollution control, protein secretion, and the production of active secondary metabolites. The evolution of gene editing technology has significantly improved the study of filamentous fungi, which in the past was laborious and timeconsuming. But recently, CRISPR-Cas systems, which utilize small guide RNA (sgRNA) to mediate clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated proteins (Cas), have demonstrated considerable promise in research and application for filamentous fungi.The principle, function, and classification of CRISPR-Cas, along with its application strategies and research progress in filamentous fungi, will all be covered in the review. Additionally, we will go over general matters to take into account when editing a genome with the CRISPR-Cas system, including the creation of vectors, different transformation methodologies, multiple editing approaches, CRISPR-mediated transcriptional activation (CRISPRa) or interference (CRISPRi), and base editors (BEs).